Avaliação do grau de consciência ambiental, do consumo ecológico e dos critérios de compra utilizados por consumidores da região central de São Leopoldo-RS - Alves, Sinara Heck (2011)
Each consumer chooses a criterion when buying a product. They are influenced maybe by greenmarketing, the logo mark, the quality, etc. However, a question arises whether, on the purchase,they are a conscious consumer and environmentally friendly. The purpose of this study is to assessthe degree of environmental awareness, consumption and environmental purchasing criteria usedby consumers in the central region of São Leopoldo- RS, Brazil. To measure this degree, weconducted an exploratory study using a questionnaire. Its implementation occurred in twodifferent groups of citizens in the downtown region. A group was formed by residents of acondominium (Group 1) and the other group was several clients of a Supermarket (Group 2) ofcity. Both groups presented similar results. The mainly criteria used is the Price when buying acommodity. They are potential consumers perceive and have traces of environmentally consciousconsumers, but are weak ecologically. Note clearly that we must work with environmental education. It’s important to review values that are in the history of each individual and provide aspace where he can reflect and transform its culture into a culture that focuses on the commongood of everyone on this planet.